Analysis of the effect of ideological education group psychotherapy combined with aromatic plant essential oil on alleviating students' anxiety disorder. (March 2023) - Zhou, Ziwei; He, Zhiyuan
Abstract : Background: Student anxiety disorder is very common today. According to the Diagnostic and Statistical Manual of Mental Disorders (DSM), it includes phobia, panic disorder, obsessive compulsive disorder, generalized anxiety disorder and post-traumatic stress disorder. The emergence of collective psychotherapy in ideological education aims to use the auxiliary role of collective combination of ideological education to appease students' anxiety, but it has not achieved good results. Aromatic plant essential oil combines aromatherapy, which can promote people's physical and mental health through inhalation or massage. Therefore, the research will integrate aromatic plant essential oil into ideological education group therapy for clinical treatment. Subjects and Methods: In this experiment, a total of 50 patients were observed, half of them were male and half female. All 50 patients reached the standard of anxiety disorder. Anxiety disorder as a mental disease α Brain waves will change. When people are in anxiety, α Brain waves will decrease or even disappear, so the study used the ND-97 digital EEG to test the left and right occipital α Brain wave changes. The experiment was conducted twice, with an interval of 7 days between the two experiments. For α Brain wave changes, the results are shown in Figure 1 . Results: The brain wave intensities of different subjects were different, while the brain wave intensities of left occipital region and right occipital region were basically consistent. But before and after smelling, the changes of brain wave are also different. In the first experiment, left and right occipital regions of 50 patients α 34 cases (68%) had enhanced brain wave; α Brain wave instability occurred in 5 cases, accounting for 10%; α the brain wave was weakened in 11 cases, accounting for 22%. After the second experiment α Brain waves were enhanced in 39 cases (78%); α Brain wave instability occurred in 7 cases, accounting for 14%; α Brain wave was weakened in 4 cases, accounting for 8%. In general, α the more patients with brain wave enhancement, it shows that the ideological education collective psychotherapy combined with aromatic plant essential oil has greatly alleviated the tension and anxiety disorders of patients, and has a certain effect. Conclusions: Anxiety disorder is quite common among today's student groups, and the traditional collective therapy of ideological education is limited for various reasons, therefore, its role in alleviating students' anxiety disorder is not obvious. As a natural therapy, aromatherapy with aromatic plant essential oil can play a very effective role in relieving students' anxiety disorder, and has a high acceptance rate for students.